Aktywność misyjna gnostyków na przykładzie walentynian - Przemysław Piwowarczyk (Vox Patrum, 2015)
The source base for the study on the Gnostic missionary activity in general is rather scarce, nonetheless in the case of the Valentinians, one of the major branches of ancient Christian gnosticism, the main characteristics of the their mission could be given with some certainty. First of all the Valentinians run the mission directed to other Christians. It was conducted by means of public teaching during the open gatherings of the Valentinian communities. The more interested were then taken aside and provided with more specific instructions. The written texts, such as letters or introductory treatises, were also in use. Valentinian mission had probably mostly educational character, because there is no source evidence for Valentinian efforts to gain new members for their own church communities. The main goal was to bring the spiritual enlightenment, divine knowledge, to brothers who did not yet received it. Of course such an enlightened Christian presumably in greater part joined the Valentinian community, however the sources do not confirm, that it was either demanded or recommended. The mission to the Pagans is not so well testified. The Valentinian texts from Nag Hammadi Codices, such as Tractatus Tripartitus and Letter to Rheginus prove that there were some converts from among the Pagans, but probably not numerous and not eagerly sought. Only the former text mentions some kind of apostles of good message, who might be recognized as those who preach to non-Christians. We do not know however, if they spread the basics of Christianity or at once its deeper Gnostic meaning.